ANALISIS DAMPAK BIMBINGAN KONSELING ISLAM DALAM MEMBENTUK KARAKTER SISWA BERBASIS NILAI-NILAI BUDAYA LOKAL - R Nurhayati; Jamaluddin, Jamaluddin; Faizah, Andi (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
This study aims to analyze the impact of Islamic counseling guidance on student character formation through the integration of local cultural values as a response to moral challenges in the era of globalization. The method used is a qualitative approach with library research techniques and thematic content analysis of various current literature on Islamic counseling guidance, character education, and local culture. The results of the study indicate that the implementation of Islamic counseling guidance integrated with local cultural values has a significant positive impact on student character formation. The integration of Islamic values such as honesty, responsibility, and patience with local wisdom such as mutual cooperation, politeness, and respect for parents has been proven to be able to shape students with noble character, culture, and high social responsibility. Counselors who understand the local cultural context of students are also more effective in building warm and trusting counseling relationships, so that the counseling process becomes more emotionally and spiritually meaningful. Students are not only helped to resolve personal problems, but also experience improvements in reflective skills, moral decision-making, and strengthening cultural identity that impacts self-confidence and nationalism. Thus, Islamic Counseling Guidance based on local culture plays an important role as a contextual, applicable, and relevant character-building instrument in facing the challenges of the times.